Potensi dan Dampak Model Pembelajaran Berbasis Integrasi Media Card Game Interaktif Audio Visual dalam Penguatan Kreativitas dan Implementasi Project-Based Learning pada Materi Seni Rupa Dua Dimensi dalam Sekolah Mitra Pendidikan Profesi Guru - Abdul Rahman Prasetyo; Fikri Aulia; Otto Fajarianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the potential and impact of the learning model based on the integration of interactive audio visual card game media in increasing creativity and implementation of Project-Based Learning (PBL) in Two-Dimensional Fine Arts materials at Teacher Professional Education Partner Schools (PPG). This model is designed to integrate technology in fine arts learning by using audio-visual-based interactive card games to enrich students' learning experiences. With a qualitative approach, this study collects data through interviews, observations, and documentation analysis. The results of the study show that the integration of this interactive media can stimulate students' creativity, increase collaboration in teams, and strengthen understanding of art concepts in the context of PBL. This model has proven to be effective in creating a more interactive and collaborative learning environment, as well as providing a more enjoyable and meaningful learning experience. This research provides recommendations for the use of technology in art education and introduces more innovative methods in two-dimensional art learning.